ANALISIS PENGETAHUAN DAN SIKAP KONSUMEN DALAM MEMBELI YOGHURT DI BANDAR LAMPUNG - Kahfindra Khalik Kabuli; Yaktiworo Indriani; Suriaty Situmorang (Lampung University, 2018)
This study aims to determine: the decision making process on purchasing liquid yogurt, the consumer's knowledge on liquid yoghurt products, and the consumers’ attitude toward the liquid yoghurt product in Bandar Lampung. This study use survai methodin which number of respondents are 96 people who are recruited by accidental sampling method. The data is collected using validited and reliabilited questionnaires,and analyzed by qualitative descriptive and Fishbein multiattribute model. The attributes used are price, taste variation, brand, volume, expiration information, packaging condition, nutritional content, advertisement, taste, halal label and ease of getting the product. The result showed that decision making on purchasing liquid yogurt was done through five stages, the average level of knowledge of liquid yogurt was 93.43%, this was in the good category. Attitude analysis showed that the attribute most favored and trusted by the consumer was halal labelin which attitude score (Ao) was 1.68Key words: Consumer attitude, knowledge, liquid yoghurt